2010
DOI: 10.1073/pnas.0912311107
|View full text |Cite
|
Sign up to set email alerts
|

An ATPase promotes autophosphorylation of the pattern recognition receptor XA21 and inhibits XA21-mediated immunity

Abstract: Cell-surface pattern recognition receptors (PRRs) are key components of the innate immune response in animals and plants. These receptors typically carry or associate with non-RD kinases to control early events of innate immunity signaling. Despite their importance, the mode of regulation of PRRs is largely unknown. Here we show that the rice PRR, XA21, interacts with XA21 binding protein 24 (XB24), a previously undescribed ATPase. XB24 promotes autophosphorylation of XA21 through its ATPase activity. Rice lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(158 citation statements)
references
References 38 publications
6
147
0
4
Order By: Relevance
“…Furthermore, there are vast differences within the plant kingdom. For example, genome analyses have revealed that rice has approximately 10 times as many non-RD RKs (328 non-RD RKs) as Arabidopsis (35 non-RD RKs) (31,48,178). It may be that the expansion of non-RD kinases in rice is representative of a divide between monocots and dicots.…”
Section: An Attempt To Define and Predict Receptors Of Conserved Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are vast differences within the plant kingdom. For example, genome analyses have revealed that rice has approximately 10 times as many non-RD RKs (328 non-RD RKs) as Arabidopsis (35 non-RD RKs) (31,48,178). It may be that the expansion of non-RD kinases in rice is representative of a divide between monocots and dicots.…”
Section: An Attempt To Define and Predict Receptors Of Conserved Micrmentioning
confidence: 99%
“…Support for this hypothesis comes from recent results showing that the ATPase XB24 promotes XA21 autophosphorylation, holding it in a biologically inactive state. Only upon ligand binding does the ATPase disassociate, triggering XA21 activation (31).…”
Section: A Predicted Functional Implication For the Non-rd Kinase Motmentioning
confidence: 99%
“…This offers the possibility for molecular cross talk between different RKmediated signaling pathways, as recently demonstrated for brassinosteroid signaling negatively impacting flg22 responses (Albrecht et al, 2012;Belkhadir et al, 2012). At the molecular level, BAK1/SERK3 was shown to transphosphorylate BRI1 and EFR (Wang et al, 2008;Chen et al, 2010;Schwessinger et al, 2011). Moreover, BRI1, FLS2, and EFR can associate with other members of the SERK family, revealing some levels of functional redundancy (Albrecht et al, 2008;Roux et al, 2011).…”
mentioning
confidence: 98%
“…The XB24/ATPase physically associates with the juxtamembrane motif of Xa21 and enhances Xa21 autophosphorylation that keeps the Xa21 protein in an inactive status [ 72 ]. Upon recognition of sulfated Ax21, the Xa21 kinase disassociates from XB24 and is activated, which results in the initiation of downstream defense responses.…”
Section: Resistance Conferred By the Mr Genes Of Lrr Receptor Kinase-mentioning
confidence: 99%